Surgical Pulmonary Embolectomy. Issue 12 (22nd September 2015) - Poterucha, Timothy J.; Bergmark, Brian; Aranki, Sary; Kaneko, Tsuyoshi; Piazza, Gregory
<x xml:space="preserve">Abstract</x> Supplemental Digital Content is available in the text.